Strategi Pengembangan TPU Dosay sebagai Ruang Terbuka Hijau Berbasis Persepsi Masyarakat dan Analisis SWOT-AHP - Ammy A. Felle; Frans A. Asmuruf; Basa T Rumahorbo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Limited land in the urban area of Jayapura Regency is a major challenge in the provision of Green Open Space (RTH), even though the existence of RTH is very important to maintain ecological balance and the quality of the community's living environment. In this context, the Dosay Public Cemetery (TPU) has great potential to be optimized as an alternative green space that is multifunctional-ecological, social, and aesthetic. This study aims to assess community perceptions of the utilization of TPU Dosay as a green space, as well as to formulate a strategy for its sustainable development. The approach used was mixed methods, with data collection through a survey using a Likert scale to 35 respondents, open interviews with 9 key informants, as well as SWOT and AHP analysis. The results showed that most people support the development of TPU Dosay as a reflective green space that is comfortable and ecologically valuable. From the results of AHP analysis, policy and regulation aspects are the top priorities in the development strategy, followed by vegetation and accessibility aspects. Strategic recommendations include the preparation of adaptive vegetation zoning, strengthening the local policy framework, active involvement of indigenous communities, and cross-sector collaboration between local governments, academics and the private sector. With the right strategy, the development of TPU Dosay is expected to be an innovative solution in overcoming the shortage of green spaces in Jayapura Regency.